Từ trải nghiệm thương hiệu điểm đến trực tuyến đến ý định giới thiệu: Vai trò trung gian của tính chân thực thương hiệu điểm đến, tình yêu thương hiệu và vai trò điều tiết của mức độ tham gia - Trương Minh , Ký; Tô Phước , Hải (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study explores the psychological mechanism that translates tourists’ viewing experiences on TikTok into recommendation intentions. It develops and tests a moderated mediation model to clarify the relationship between destination brand experience and recommendation intention. The proposed model posits that the impact of destination brand experience is sequentially mediated by destination brand authenticity and brand love, with involvement acting as a moderator. Grounded in the S-O-R framework, the research surveyed 455 young Vietnamese tourists who had watched TikTok videos featuring the Ninh Binh destination. Data were analyzed using PLS-SEM. The findings reveal that destination brand experience positively influences destination brand authenticity, brand love, and recommendation intention. Furthermore, the study confirms a sequential mediation mechanism wherein positive online experiences enhance perceived authenticity, foster brand love, and ultimately drive recommendation intentions. Additionally, involvement was found to strengthen these effects. This research extends the S-O-R theory within the context of digital tourism marketing and offers managerial implications for designing video content to optimize user engagement and foster brand advocacy behaviors.